(untitled) (Research, Society and Development, 2021)
The following meta-analysis aims to evaluate the position of mandibular third molars and their nearby anatomical structures (lower dental canal, lower dental nerve, lingual cortex, lower second molar). It was performed using a filter that allows the classification and evaluation of various scientific articles, applying an advanced search through digital databases such as Pubmed, Cochrane, Science Direct and Wiley, the selected articles should be published between 2017-2021. In addition, we detail the different classifications used to evaluate an impacted mandibular third molar, which according to Winter the most prevalent position is the mesioangular and according to Pell and Gregory there is a higher prevalence of Class 2-B; we also detail recent classifications for impacted molars such as "Liqun Gu" and "Ogüz Boraham". These findings illustrate the importance of locating structures close to the mandibular third molar, knowing different classifications to determine the position of an impacted third molar and the advantage of CBCT in surgical planning, thus avoiding possible iatrogenesis in clinical practice.